The relationship between digital literacy and critical thinking skills of SMAN 1 Pundong students on the digestive system - Saputri, Rohmi Dwi; Kurniawati, Atik (Universitas Negeri Yogyakarta, 2026)
This study aims to (1) determine the digital literacy of students of SMA Negeri 1 Pundong in biology learning on the topic of the digestive system; (2) determine the critical thinking skills of students of SMA Negeri 1 Pundong in biology learning on the topic of the digestive system; (3) determine the relationship between digital literacy and critical thinking skills of students of SMA Negeri 1 Pundong in biology learning on the topic of the digestive system. The type of research used is correlational research. Data collection techniques included tests, questionnaires, interviews, and analysis of learning documents. The research subjects were 74 students of class XI MIPA of SMA Negeri 1 Pundong. The sampling method in this study was saturated sampling. Data analysis used descriptive analysis and also Pearson product-moment correlation analysis. The results of the analysis showed that: 1) Digital literacy of students of SMA Negeri 1 Pundong in the moderate category (42%); 2) Critical thinking skills of students of SMA Negeri 1 Pundong in the moderate category (47%); 3) There is no relationship between digital literacy and critical thinking skills of students of SMA Negeri 1 Pundong, with a sig value 0.05 (0.167 0.05). The results of this study indicate that increasing digital literacy has not automatically led to improved critical thinking skills, so a biology learning design is needed that explicitly integrates digital literacy activities with problem-based learning strategies, inquiry, or HOTS-based learning to more effectively stimulate critical thinking skills.